ASSESSMENT OF THE EFFECTIVENESS OF BANK RESOLUTION IN UKRAINE - STEPANETS, Victoria; KRASNOVA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
For Ukraine, in the context of economic turbulence and uncertainty in the financial market, an important task is to find ways to prevent situations where losses from the liquidation of insolvent banks constitute a much larger share of the proceeds from the sale of assets of failed banks. In view of this, an important task is to transform the system of bank resolution, including the choice of resolution methods as opposed to liquidation, as well as to improve approaches within these procedures to the management and sale of assets of insolvent banks. As part of this approach, it is important to ensure that the resolution method is chosen to maximize the satisfaction of the bank's creditors claims and to determine a fair and high-quality valuation of bank assets.The authority to resolve banks has been transferred to the Deposit Guarantee Fund, which is guided by the methods of bank resolution specified by law. However, most of the domestic insolvent banks were liquidated. Depositors, creditors, the banking system, and the DGF suffered significant economic losses, reputational risks, and a loss of confidence in banks and supervisory and resolution authorities. In order to avoid such negative consequences in the future, it is necessary to look for ways to resolve these issues today, in the martial law crisis conditions.The paper proposes an author's methodology for assessing the effectiveness of bank resolution. The paper uses actual practical material to assess the effectiveness of procedures of the sale of assets of insolvent banks and for which no resolution methods have been applied. It is proved that not all assets can be sold at appraised value. Based on the results of comparing the appraised value of assets and the investor's price (tender offer), it turns out that sometimes it is more expedient to accept an investor's offer that is lower than the appraised value at the stage of an open tender than to sell such assets in the future at an even lower price than the investor's price. In this case, the Fund, and thus the depositors, will suffer a loss of economic benefit.
Keywords: assets; valuation; resolution methods; bank; liquidation; regulation; sale; efficiency; investor